2015
DOI: 10.1007/s10551-015-2759-1
|View full text |Cite
|
Sign up to set email alerts
|

Board Gender Diversity and Corporate Response to Sustainability Initiatives: Evidence from the Carbon Disclosure Project

Abstract: This paper investigates the effect of female representation on the board of directors on corporate response to stakeholders' demands for increased public reporting about climate change-related risks. We rely on the Carbon Disclosure Project as a sustainability initiative supported by institutional investors. Greenhouse gas emissions measurement and its disclosure to investors can be thought of as a first step toward addressing climate change issues and reducing the firm's carbon footprint. Based on a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
627
13
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 688 publications
(843 citation statements)
references
References 81 publications
(97 reference statements)
62
627
13
10
Order By: Relevance
“…In order to understand the effect that women have on boards, it is important to consider not only their presence, but also their number. Given this fact, researchers (Prado-Lorenzo and Garcia-Sanchez, 2010;Lio et al, 2014;Ben-Amar, et al, 2015) have examined the effect of gender diversity on GHG emissions disclosures with mixed results. They also reveal that board gender diversity with more than two women directors influences board disclosures on GHG emission levels and climate change strategies.…”
Section: Australian Emissions Trading Scheme (Aets) and Carbon Disclomentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand the effect that women have on boards, it is important to consider not only their presence, but also their number. Given this fact, researchers (Prado-Lorenzo and Garcia-Sanchez, 2010;Lio et al, 2014;Ben-Amar, et al, 2015) have examined the effect of gender diversity on GHG emissions disclosures with mixed results. They also reveal that board gender diversity with more than two women directors influences board disclosures on GHG emission levels and climate change strategies.…”
Section: Australian Emissions Trading Scheme (Aets) and Carbon Disclomentioning
confidence: 99%
“…Nevertheless, scholars have found a larger board to be better (Gales and Kesner, 1994;Dalton et al, 1999). In this case, the climate change risk issue could be considered by larger number of board members as their background skills (education, experience) help of understanding and evaluating a firm's social roles ( Chang et al, 2015). They can bring a wealth of knowledge and experience to the board and can also increase the element of independence and objectivity in the board's strategic decision-making (Fama and Jensen, 1983).…”
Section: Size Of the Board Of Directorsmentioning
confidence: 99%
“…Additionally, a directive was proposed which established that at least 40% of non-executive board positions should be held by women [36]. Also, Post et al [33] contended that a higher female representation on a board lead to the foundation of sustainability-themed alliances, whereas Ben-Amar et al [37] found an improvement of disclosure on voluntary climate change in companies showing greater women ratio on boards.…”
Section: Hypothesis 5 (H5)mentioning
confidence: 99%
“…Increased diversity on forest sector company boards and TMTs may be a way to further develop market and customer orientation, as well as innovation (Hansen and Breede 2016). Others show that the percentage of females on boards is related to voluntary sustainability related actions, another sign of being in tune with the marketplace (Ben-Amar et al 2015).…”
Section: Discussionmentioning
confidence: 99%